Electrochemical Deposited Calcium Phosphate Nanomaterials with Micro‐Nano Interface for Capture and Non‐Invasive Release of Cancer Cells. Issue 23 (10th November 2021) - Zhang, Kelin; Zhang, Qilin; Yu, Mingxia; Wang, Zixiang; Song, Qingyuan; Zhu, Cuiwen; Wu, Xianjia; He, Rongxiang; Zhao, Xingzhong
Abstract: A low cost and easily fabricated 3D micro‐nano biocompatible calcium phosphate (CaP) microstructure platform is developed to efficiently capture and non‐destructively release cancer cells. The thickness of CaP is ≈3 µm after 2.5 min deposition and increased to ≈12 µm after 10 min deposition. The void size between CaP nanosheets is increased when the electro deposition time is increased. This micro‐nano bio‐interface is suitable for cancer cell capturing and culturing. More than 90% for the EpCAM positive cells are captured on the CaP substrates where the specific anti‐EpCAM antibody is modified. On the other hand, the CaP substrates are easily degraded in citric acid (pH 6.0). In this method, 80% of the captured cancer cells can be rapidly released in 2.5 min on the 3 µm thick CaP substrates. The released cancer cells can be well cultured and can keep their viability. This platform is successfully used to capture the CTCs from patients' peripheral blood with different kinds of cancer. This platform can be applied in the controllable single CTC capture and release analysis, including downstream RT‐PCR, gene sequence, and single cell based tumor sphere culture in the future. Abstract : Calcium‐phosphate nanomaterials with micro‐nano biointerface are electrochemically deposited on the fluorine‐doped tin oxide glass surface. This biointerface modified with anti‐EpCAM antibody shows high tumor cells capture efficiency, up to 93%. The captured cells are released by dissolving calcium‐phosphate materials using citric acid solution (pH 6.0, 10 mm ). This platform is successfully applied to isolate CTCs from cancer patients' peripheral blood.